Financial Inclusion dan Financial Exclusion di Perbankan Syariah - Ahmad Rodoni; Novia Nengsih; Lili Supriyadi (JURNAL INDO-ISLAMIKA, 2016)
This paper delvs a set of ‘financial exclusion’ factors in the Syari`ah (Islamic-law based) banking and measures its inclusive financial index. The financial exclusion is a condition, in which society has an obstacle to have an access into a financial institution. In contrast, the ‘financial inclusion’ is a process, in which a financial institution paves an access into a formal financial institution for unbankable people. This study is descriptive and qualitative. That is, the qualitative analysis uses the analytical technique data developed by Miles and Huberman (2009), such as data reduction, data display, and drawing or verivication of conclusion. Meanwhile, Quantitative analysis uses an Inclusive Financial Index (Indeks Keuangan Inklusif/IKI), such as dimensions attributed to the banking services, such as access, element of usage, and component of quality. This research employs primary resources resulted from interview and macro economic data, particularly sector of banking services. Additionally, this paper also refers to its secondary resources, such as financial report of Syari`ah banking dated from 2014 to 2016, and findings of diverse resources in terms of data, journals, books, and others connected to this study.